Các yếu tố tác động tới mức độ sẵn sàng xuất khẩu của doanh nghiệp nhỏ và vừa tại Việt Nam - Nguyễn Thị Phương, Chi; Nguyễn Thị Phương, Dung; Đỗ Hoài, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The present study is conducted to measure the readiness to export of small and medium enterprises (SMEs) in Vietnam and examine its determinants. By surveying 200 Vietnamese exporting SMEs, research results show that the readiness to export of an enterprise is reflected in terms of organization and product. Four factors directly impact company export potential are internal export stimulus, external export stimulus, inward internationalization, and pre-export preparation activities. The study provides managerial implications and recommendations for enterprises as well as policy-makers.